TO COMPARE CERVIX RIPENING (USING MODIFIED BISHOP SCORE) BETWEEN PROSTIN E2 AND LAMINARIA + PROSTIN E2 IN WOMEN UNDERGOING INDUCTION OF LABOUR - Dr Hina Mushtaq; Dr Sana Ghaffar Bajwa; Dr Nida Arif; Dr Sobia Haneef; Dr Komal Tariq; Dr Lubna Bibi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: To compare cervix ripening between laminaria+Prostin E2 and Prostin E2 alone in women undergoing induction of labour. Study design: Randomized controlled trial.Place and duration of study: This study was conducted at the MCH Center, Unіt-II, Pakistan Institute of Medical Sciences, Islamabad from 1st of November 2020 to 30th of April 2021.   Methods: A total of 132 pregnant women with 37-42 weeks of gestation having singleton pregnancy and planned for induction of labour with unfavorable cervix (bishop score